Dari Kesiagaan Menuju Kinerja Global: Tinjauan Literatur Kualitatif atas Jalur Strategis Internasionalisasi UKM melalui Kesiagaan Kewirausahaan dan Kapabilitas Dinamis - Moh Trisamanta; Erwin Santosa; Moh Zalmi Kahardani (Studia Ekonomika, 2026)
This qualitative literature review explores the strategic pathways through which entrepreneurial alertness and dynamic capabilities contribute to the international performance of small and medium enterprises (SMEs). Drawing from recent conceptual and empirical studies, the review highlights how opportunity recognition (alertness), decision-making logics (causation and effectuation), and dynamic capabilities (sensing, seizing, and reconfiguring) interact to support SMEs' global expansion efforts. The findings indicate that internationalization is not a linear process but a dynamic interplay of cognitive, strategic, and organizational elements. This synthesis contributes to the theoretical integration of entrepreneurship and international business literature and provides practical implications for SME managers and policymakers seeking to enhance global competitiveness through adaptive capability-building strategies.